Anion induced displacement studies in naphthalene diimide containing interpenetrated and interlocked structures - Mullen, K; Davis, J; Beer, P (2009)
This article describes investigations into the development of supramolecular systems capable of sensing anions through either displacement type assays or molecular motion. An electron deficient naphthalene diimide thread and an electron rich isophthalamide naphthohydroquinone macrocycle were shown to form a coloured pseudorotaxane assembly. Investigations into the ability of such interpenetrated systems to sense anions colorimetrically were undertaken. Anion complexation at the isophthalamide group of the macrocycle causes displacement of the naphthodiimide thread resulting in the loss of colour. The enhanced mechanically bonded binding strength between the naphthodiimide axle and the naphthohydroquinone groups of the macrocycle wheel in the corresponding rotaxane structure, however, was found to negate the anion induced displacement process. © 2009 The Royal Society of Chemistry.